Analisis Strategi Marketing Mix Dalam Meningkatkan Pengiriman Barang dan Jasa: : Studi pada PT. JNE Express Cabang Patumbak - Fauzi Ahmad Romadhon; Zuhrinal M. Nawawi (Economic Reviews Journal, 2022)
The purpose of this research is to study how the marketing strategy of PT.JNE Express Patumbak Branch was developed and how the marketing strategy of PT.JNE Express Patumbak Branch was implemented. This research is a descriptive field study with a deductive model, conducted through structured and unstructured interviews. In addition to collecting data through observation, data management is carried out through methods of organization, organization, and analysis. This research is a quantitative research. Based on the results of a survey conducted by PT.JNE Express Patumbak Branch on products, prices, locations, promotions, people, physical assets, and strategic processes. The product strategy is assisted by the availability of flexible products such as Yes, Normal, and Economic Status (OK) that are tailored to customer needs. JNE Express has 14 products and services, with prices based on quantity and quality. Packages of socialization, expansion of partnerships, franchising, promotion of law and order training, online advertising and internet marketing, strategies for community empowerment programs (HR for employees), and employee benefits in materials and information. Have a good communication, writing, and information strategy physically, as well as a good process strategy, good communication channels, and good technology-oriented services. Keywords: marketing strategy, internet marketing, JNE